(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The interaction of molybdenum (VI) with citric acid is studied by the methods of ion exchange and spectral photometry. It is determined that the complex formation takes place in discrete steps to MoO^2+_2 HC6H5O^2-_7 equal to 1:1 and 1:2 at ionic force μ=1 and at temperature 20℃. Stepwise and general stability constants for the complexes are defined.